Preliminary Study of Intravenous Amantadine Treatment for Ataxia Management in Patients with Probable Multiple System Atrophy with Predominant Cerebellar Ataxia - Jinyoung Youn; Hyeeun Shin; Ji Sun Kim; Jin Whan Cho (Journal of Movement Disorders, 2012)
Background and Purpose: Multiple system atrophy with predominant cerebellar ataxia is a disabling neurologic disease. However, effective management has not yet been established. We conducted a short-term, open-label preliminary study to assess the benefits of intravenous amantadine treatment in patients with probable multiple system atrophy with predominant cerebellar ataxia. Methods: Twenty patients (10 male, 10 female) with probable multiple system atrophy with predominant cerebellar ataxia received 400 mg of amantadine by intravenous per day for 5 days. Ataxia severity was evaluated by the International Cooperative Ataxia Rating Scale before and after intravenous amantadine therapy and all subjects reported subjective improvement after intravenous amantadine treatment using a patient global impression scale. We analyzed the total and subscale scores by the ataxia scale and patient global impression scale. Results: The mean age was 57.4 years (range: 47–72) and the mean disease duration was 30.8 months (range: 11–79). The ataxia severity significantly decreased after intravenous amantadine therapy from 42.5 to 37.3 (p < 0.001). The mean patient global impression scale for improvement was 2.9 and there were no side effects of intravenous amantadine treatment observed. When we assessed responders, the duration of intravenous amantadine effect was more than 1 month in 4 subjects of 7 responders. Conclusions: Our findings suggest that intravenous amantadine treatment can be a safe management option in cerebellar ataxia, although the mechanism is unclear. Thus, further double-blind, long-term studies with a larger sample size are needed.